2014
DOI: 10.3390/ijerph111212611
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lifestyle on the Incidence of Dental Caries among 3-Year-Old Japanese Children

Abstract: The present cohort study examined how lifestyle, household environment, and caries activity test score of Japanese children at age 1.5 years affected their dental caries incidence at age 3. Inclusion criteria were 1.5-year-old children with no dental caries. Dental examinations were performed for 33,655 children who participated in routine dental examinations at 1.5 years of age, and the exam was repeated approximately 21 months later (at age 3) at the Kobe City Public Health Center in Japan. After excluding 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 31 publications
(49 reference statements)
7
61
3
3
Order By: Relevance
“…Although our results confirmed those of other studies showing an effect of ETS exposure at home on dental caries [Williams et al, 2000;Aligne et al, 2003;Shenkin et al, 2004;Tanaka et al, 2006;Hanioka et al, 2008;Leroy et al, 2008;Tanaka et al, 2009;Tanaka and Miyake, 2012;Watanabe et al, 2014;Nakayama and Mori, 2015;Nakayama and Mori, 2017], other studies investigated the effect of ETS on ECC only.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although our results confirmed those of other studies showing an effect of ETS exposure at home on dental caries [Williams et al, 2000;Aligne et al, 2003;Shenkin et al, 2004;Tanaka et al, 2006;Hanioka et al, 2008;Leroy et al, 2008;Tanaka et al, 2009;Tanaka and Miyake, 2012;Watanabe et al, 2014;Nakayama and Mori, 2015;Nakayama and Mori, 2017], other studies investigated the effect of ETS on ECC only.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, it was suggested that children exposed to environmental tobacco smoke (ETS) have an increased risk of dental caries in deciduous dentition [Williams et al, 2000;Aligne et al, 2003;Shenkin et al, 2004;Tanaka et al, 2006;Hanioka et al, 2008;Leroy et al, 2008;Tanaka et al, 2009;Tanaka and Miyake, 2012;Watanabe et al, 2014;Nakayama and Mori, 2015;Nakayama and Mori, 2017]. Aligne et al [2003] reported that an elevated serum cotinine level was significantly associated with an increased risk of both decayed and filled teeth of US children from 4 to 11 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…SSB consumption and adverse dental health outcomes have been associated in children. 45–48 However, study results of tooth loss, SSB consumption in adults with and without DM have not been previously presented in peer-reviewed journals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 55% of children and adolescents in the sample consumed more than 1 serving of SSB daily, while up to 21% did not drink water on a daily basis in some countries (unpublished data). This raises concern since the negative consequences of SSB consumption on children's health have been highlighted in numerous studies demonstrating that children who consume one or more SSB serving per week have a 50-80% increased risk of dental caries, overweight and obesity, and metabolic syndrome compared with non-or sporadic consumers of SSB [26][27][28][29][30][31][32][33].…”
Section: Water and Fluid Intake Habits Of Childrenmentioning
confidence: 99%